THE INFLUENCE OF VARIOUS RISK FACTORS ON THE CORRELATION BETWEEN HPV INFECTION AND THE ADVANCEMENT OF CERVICAL CARCINOMA - BUKHARI, NT; JABEEN , S; JABEEN, U; NISA, I; KHAN, UA; LIAQAT, A; FAROOQ, S; ZAMAN, K; SHIREEN, F; AYAZ, M (Biological and Clinical Sciences Research Journal, 2024)
Cervical cancer is a significant global health challenge, disproportionately impacting women in developing nations, where approximately 85% of incidence and mortality occur. The primary etiological agent is the human papillomavirus (HPV), with high-risk types HPV 16 and 18 accounting for over 90% of cases. Despite the high prevalence of HPV, most infected women do not develop cervical cancer, indicating the role of additional risk factors. Objective: This study aims to investigate the association between various sociodemographic and behavioral factors, HPV infection, and the progression of cervical cancer. Methods: This case-control study was conducted at the Cancer Care Hospital and Research Center in Pakistan from April 2024 to April 2024. It involved 200 consecutive subjects, with 100 cases diagnosed with precancerous lesions (HSIL/LSIL) or invasive carcinoma of the uterine cervix, and 100 age and ethnicity-matched controls with normal cervical cytology. Data were collected through structured personal interviews and analyzed using descriptive and inferential statistical methods. The significance level was set at p < 0.05. Results: Significant differences between cases and controls were observed in dietary habits, gravidity, parity, age, menopausal status, residential setup, tobacco chewing, smoking, and age at marriage. Non-vegetarian diet, higher gravidity and parity, older age, postmenopausal status, rural residence, tobacco use, and early marriage were significantly associated with increased cervical cancer risk (p < 0.0001). No significant difference was found in literacy rates (p = 0.68). Conclusion: The study highlights the multifactorial etiology of cervical cancer, emphasizing the need for targeted interventions addressing specific risk factors. Early detection, HPV vaccination, and public health education, particularly in rural areas, are crucial for reducing cervical cancer burden.